Cash buffer and government securities issuance policy: An ARDL analysis of Indonesia’s fiscal coordination - Pramana, Kukuh Sukma; Safuan, Sugiharso (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Indonesia’s fiscal policy is characterized by a persistent budget deficit, whereby government spending structurally exceeds revenues. To finance this gap, the government issues short-term government securities (GS). However, GS issuance generates interest expenses and may lead to idle cash accumulation in subsequent periods, raising concerns for GS management. Accordingly, this study investigated the extent to which government cash balances influence short-term GS issuance in Indonesia. Using quarterly data from 2015 to 2023, the autoregressive distributed lag (ARDL) model was employed, supported by descriptive analysis, unit root testing, and robustness checks. Results indicate a linear relationship between GS issuance and cash balance. In particular, an increase in cash balances will also increase GS issuance. Therefore, debt and cash managers must coordinate to increase the effectiveness of budget deficit financing through GS issuance and state cash management. The study contributes to the literature by highlighting the role of cash stability in shaping debt issuance behavior. Policy implications emphasize the need for stronger coordination between debt and cash managers to improve financing efficiency, minimize idle balances, and ensure sustainable fiscal discipline in government securities management.